Co-trimoxazole as prophylaxis against opportunistic infections in HIV-infected Zambian children (CHAP): a double-blind randomised placebo-controlled trial. - Chintu, C; Bhat, G; Walker, A; Mulenga, V; Sinyinza, F; Lishimpi, K; Farrelly, L; Kaganson, N; Zumla, A; Gillespie, S; Nunn, A; Gibb, D (2004)
BACKGROUND: No trials of co-trimoxazole (trimethoprim-sulfamethoxazole) prophylaxis for HIV-infected adults or children have been done in areas with high levels of bacterial resistance to this antibiotic. We aimed to assess the efficacy of daily co-trimoxazole in such an area. METHODS: We did a double-blind randomised placebo-controlled trial in children aged 1-14 years with clinical features of HIV infection in Zambia. Primary outcomes were mortality and adverse events possibly related to treatment. Analysis was by intention to treat. FINDINGS: In October, 2003, the data and safety monitoring committee recommended early stopping of the trial. 541 children had been randomly assigned; seven were subsequently identified as HIV negative and excluded. After median follow-up of 19 months, 74 (28%) children in the co-trimoxazole group and 112 (42%) in the placebo group had died (hazard ratio [HR] 0.57 [95% CI 0.43-0.77], p=0.0002). This benefit applied in children followed up beyond 12 months (n=320, HR 0.48 [0.27-0.84], test for heterogeneity p=0.60) and across all ages (test for heterogeneity p=0.82) and baseline CD4 counts (test for heterogeneity p=0.36). 16 (6%) children in the co-trimoxazole group had grade 3 or 4 adverse events compared with 18 (7%) in the placebo group. These events included rash (one placebo), and a neutrophil count on one occasion less than 0.5x10(9)/L (16 [6%] co-trimoxazole vs seven [3%] placebo, p=0.06). Pneumocystis carinii was identified by immunofluorescence in only one (placebo) of 73 nasopharyngeal aspirates from children with pneumonia. INTERPRETATION: Our results suggest that children of all ages with clinical features of HIV infection should receive co-trimoxazole prophylaxis in resource-poor settings, irrespective of local resistance to this drug.